DETERMINATION OF PROPER MOTIONS OF CIRCUMPOLAR STARS BY USING IMAGES FROM UKRVO PLATE ARCHIVES - Protsyuk, Yu.; Andruk, V.; Mazhaev, A.; Kovylianska, O.; Protsyuk, S.; Golovnya, V. (Одеські астрономічні публікації, 2016)
UkrVO plate archives contain information obtained at different time periods and in different observatories for the same regions of the sky [3, 5, 6, 7, 8]. It allows us to carry out joint processing of plates and to receive new results for interesting objects. To obtain proper motions of stars in circumpolar areas, we selected 34 photographic plates from the RI NAO archive and 161 plates from the archive of the MAO NAS. A mean epoch difference between the plates from these archives is 55 years. Scanning of the plates and data processing were independently carried out by both observatories. A catalog of equatorial positions for 195 thousand stars up to 15m was compiled in the RI NAO (black dots in Fig. 1). A catalog of equatorial positions for 1050 thousand stars up to 16.5m was compiled in MAO (gray dots in Fig. 1). A comparison of positions for common stars contained in these catalogs was conducted. A catalog of proper motions for 30 thousand common stars up to 15m was compiled using these two input catalogs. The obtained result suggests the advisability of processing of all observations to receive proper motions of stars up to 14-15m in the declination zone of 65° to 90°.